THE ANALYSIS OF IMPLEMENTATION OF THE CONSOLIDATED TAX SYSTEMS ABROAD - V. Alkaeva (Publishing House of the State University of Management, 2016)
The article gives brief characteristics of consolidated tax systems applicable in foreign countries. The comparative analysis of foreign tax consolidation regimes with Russian regime applicable from 2012 is presented. Based on foreign experience it is suggested ways to overcome the reduction of profit tax to the budgets of different regions of Russian Federation because of function of consolidated groups.